Risk analysis of intracranial aneurysm rupture based on the arterial segment of origin - Feng, Junqiang; Tang, Yudi; You, Wei; Jiang, Yuhua; Xu, Zhengkun; Zhao, Yan; Liu, Xinke; Lv, Jian; Liu, Peng; Wei, Haining; Mossa-Basha, Mahmud; Li, Youxiang; et al. (Frontiers in Neurology, 2024)
Background and Objectives Intracranial aneurysm’s (IA) rupture risk is related to its arterial origin, but whether the different segment of the artery has different risk and act as an independent risk factor, is still unknown. Our study aims to investigate the rupture risk of IAs in different artery segment in a large Chinese cohort. Methods Imaging and clinical data of consecutive patients with IAs diagnosed by CTA from January 2013 to December 2022 were collected. Two neuroradiologists independently identified ruptured and unruptured IAs based on imaging and medical record. Internal carotid artery(ICA), middle cerebral artery(MCA), anterior cerebral artery(ACA), vertebral artery(VA) and posterior cerebral artery(PCA) were segmented according to Bouthillier and Fischer Segmentation Methods. Stenoses of proximal parent vessel were evaluated and documented. The Institutional Review Board (IRB) at Beijing Tiantan Hospital approved this retrospective study. Results A total of 3,837 aneurysms (median size 3.5mm [IQR 2.6-5.1mm]; 532 ruptured) were included in this study, from 2,968 patients (mean age 57 [IQR 50-64]; 1,153 male). Ruptured aneurysms were most commonly located in the PICA (52.9%), Acom (33.8%), other locations (33.3%), ACA (22.4%), and BA (21.4%). The locations with the highest likelihood of rupture were the C7 ICA (21.3%), M2 MCA (24.0%), distal MCA (25.0%), and A2 ACA (28.1%). IAs originating from the C7 (p<0.001), dM1 (p=0.022), and dA1 (p=0.021) segments were independent risk factors for rupture. IAs without stenosis of the proximal parent vessel were associated with a higher risk of rupture (p=0.023). Conclusions There are unique associations between aneurysm origin from various arterial segments. Aneurysms origin from AcoA, BA, PICA, A2, dA, C7 and M2 indicate higher rupture risk. Aneurysms originating from C4, C5 and C6 indicate a lower rupture risk. C7 IAs, AcoA IAs and PICA IAs seems to be an independent risk factor.